Hirschsprung's Disease in the Preterm Infant: Implications for Diagnosis and Outcome. Issue 7 (July 2013) - Baxter, Katherine J.; Bhatia, Amina M.
Hirschsprung's disease (HD), congenital absence of ganglion cells, is considered uncommon in preterm infants. The aim was to describe the frequency, presentation, and surgical outcomes of preterm infants with HD. A retrospective cohort study was conducted of all patients diagnosed with HD from 2002 to 2012 at a single children's hospital. Clinical presentation and surgical outcomes were obtained for term (37 weeks of gestation or greater) and preterm infants. One hundred twenty-nine subjects with HD were identified, 24 (19%) preterm and 105 (81%) term. Preterm infants were more likely to be diagnosed after 30 days of life (66.7 vs 37.1%, P < 0.01; median age 2.9 vs 0.3 months, P < 0.05) and to have associated major congenital anomalies (45.8 vs 20.0%, P < 0.01). Fewer preterm infants had primary pull-through operations (45.8 vs 76.2%, P < 0.005). Preterm infants were more likely to have an episode of Hirschsprung's-associated enterocolitis (45.8 vs 24.0%, P < 0.05) but were not more likely to die from any cause (8.3 vs 5.8%, P = 0.64). HD may be more common in preterm infants than previously recognized, and increased comorbidities in these patients may lead to delayed diagnosis and increased morbidity. HD should be considered in the preterm infant presenting with a bowel obstruction, especially when accompanied by associated anomalies.